2019
DOI: 10.3390/cells8121582
|View full text |Cite
|
Sign up to set email alerts
|

B-RAFV600E Inhibitor Dabrafenib Attenuates RIPK3-Mediated Necroptosis and Promotes Functional Recovery after Spinal Cord Injury

Abstract: The receptor-interacting protein kinase 3 (RIPK3) is a key regulator of necroptosis and is involved in various pathologies of human diseases. We previously reported that RIPK3 expression is upregulated in various neural cells at the lesions and necroptosis contributed to secondary neural tissue damage after spinal cord injury (SCI). Interestingly, recent studies have shown that the B-RAFV600E inhibitor dabrafenib has a function to selectively inhibit RIPK3 and prevents necroptosis in various disease models. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The serine/threonine kinase B-Raf V600E inhibitor dabrafenib is the only type I RIPK3 inhibitor approved for clinical use (Rheault et al, 2013;Li et al, 2014;Sugaya et al, 2019). Previous studies have reported that dabrafenib is a selective RIPK3 inhibitor in various models, including human hepatocytes (Li et al, 2014), mouse models of acetaminophen-caused liver injury (Li et al, 2014), and ischemic brain injury (Cruz et al, 2018).…”
Section: Implications For Anti-fibrotic Therapymentioning
confidence: 99%
“…The serine/threonine kinase B-Raf V600E inhibitor dabrafenib is the only type I RIPK3 inhibitor approved for clinical use (Rheault et al, 2013;Li et al, 2014;Sugaya et al, 2019). Previous studies have reported that dabrafenib is a selective RIPK3 inhibitor in various models, including human hepatocytes (Li et al, 2014), mouse models of acetaminophen-caused liver injury (Li et al, 2014), and ischemic brain injury (Cruz et al, 2018).…”
Section: Implications For Anti-fibrotic Therapymentioning
confidence: 99%
“…The previous studies mainly discussed the role of RIPK3-mediated necroptosis in secondary SCI, but few studies further explored the effects of regulating RIPK3 on neuroinflammation and pain. Sugaya et al ( 2019 ) found that RIPK3 modulation prevented necroptosis of various nerve cells at the lesion site and favored neuroprotection. Dabrafenib treatment, one of the RIPK3 inhibitors, also promoted the recovery of motor function and sensory function after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the combined use of TMS and BMSCs is more effective compared with either therapy alone in treating SCI is not completely understood. Raf inhibition has also been reported as a potential therapeutic strategy for SCI ( 30 ), but whether the combination of TMS and Raf inhibition displays synergistic effects on SCI recovery requires further investigation. Therefore, the present study aimed to compare the effects of TMS, BMSC transplantation, RafI, TMS+BMSCs and TMS+RafI treatment on SCI in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Raf/MEK/ERK signaling is also involved in neuronal apoptosis in the hippocampus following subarachnoid hemorrhage ( 28 ). Previous studies revealed that Raf/MEK/ERK signaling was upregulated in SCI model rats ( 29 ), and that the Raf inhibitor dabrafenib displays potential to facilitate SCI recovery ( 30 ). Therefore, the present study aimed to investigate the feasibility of allogenic BMSCs and Raf inhibition for SCI treatment.…”
Section: Introductionmentioning
confidence: 99%